Etching of glass and glass-ceramics in molten salts containing hydroxides

By using alkali metal hydroxide eutectic melt mixture with a temperature of 170°C to 300°C as an etchant, the problem of slow etching speed and unenvironmental protection in the prior art is solved, and fast and environmentally friendly substrate etching is achieved and strength is improved.

CN113905995BActive Publication Date: 2025-04-25CORNING INC
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202080040392.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2019-05-31
Filing Date
2020-05-28
Publication Date
2025-04-25
Estimated Expiration
2040-05-28

AI Technical Summary

Technical Problem

Prior art When etching glass, glass ceramics and ceramic products, hydrofluoric acid or high pH aqueous hydroxide solution is used, resulting in slow etching speed, high temperature required and unenvironmental protection.

Method used

Eutectic melted mixture of alkali metal hydroxides with a temperature of 170°C to 300°C is used as the etchant to avoid the use of hydrofluoric acid, improve the etching speed and enhance environmental protection.

Benefits of technology

Fast and environmentally friendly substrate etching is achieved, the stability of the etching rate is maintained, and the strength of the substrate after etching is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN113905995B_ABST
    Figure CN113905995B_ABST
Patent Text Reader

Abstract

The method of etching a substrate comprises: contacting a substrate having a thickness with an etchant disposed in a container for a period of time until the thickness is reduced by at least 2 μm and at an average rate of 1 μm per minute to 6.7 μm per minute, the etchant having a temperature of 170° C. to 300° C. and comprising a molten mixture of two or more alkali metal hydroxides; and stopping contacting the substrate with the etchant. In some cases, the etchant comprises a molten mixture of NaOH and KOH. For example, in some cases, the etchant comprises a molten mixture of 24 wt % to 72 wt % NaOH and 76 wt % to 28 wt % KOH. In some cases, the method reduces the NaOH content in the surface composition of the substrate to 0.1 wt %. + , K + and Li + The weight percentage change is less than 1%.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] This application claims the benefit of priority under 35 USC §119 to U.S. Provisional Application Serial No. 62 / 855,327, filed on May 31, 2019, the contents of which are hereby relied upon and incorporated herein by reference in their entirety. Technical Field

[0002] The present disclosure generally relates to methods of etching glass, glass ceramics, and ceramic articles with an etchant that does not utilize hydrofluoric acid (HF), but rather utilizes a molten mixture of two or more of alkali metal hydroxides at elevated temperatures. Background Art

[0003] Glass, glass ceramics and ceramic substrates are used for various purposes in consumer electronics, such as covering displays. In some cases, substrates are prepared to be thicker than the thickness required for specific applications. Similarly, in some cases, substrates are provided with textures (e.g., by sandblasting) to impart surface features to improve tactile response or impart anti-glare properties, but the strength of the substrate is also reduced. So far, by etching substrates with hydrofluoric acid or high pH hydroxide aqueous solutions, the thickness of the substrate has been reduced, and the strength of the substrate has been restored. However, etching substrates with high pH hydroxide aqueous solutions is too slow for output and requires relatively high temperatures, and etching substrates with hydrofluoric acid may not be the most environmentally friendly. Summary of the invention

[0004] The present disclosure solves this problem by etching the substrate with a eutectic molten mixture of alkali metal hydroxides at a temperature of 170°C to 300°C. Etching the substrate with a eutectic molten mixture of alkali metal hydroxides avoids the use of hydrofluoric acid and is therefore more environmentally friendly. In addition, etching the substrate with a eutectic molten mixture of alkali metal hydroxides is faster than etching with an aqueous solution of a high pH hydroxide, so large quantities of products can be produced within a commercially viable time period. In addition, experiments have shown that the eutectic molten mixture of alkali metal hydroxides maintains the ability of the substrate to be repeatedly etched at approximately the same etching rate. Moreover, experiments have shown that the textured substrate etched with the eutectic molten mixture of alkali metal hydroxides is stronger than the textured substrate etched with a high pH aqueous hydroxide solution, and has a strength similar to that of the untextured substrate.

[0005] According to a first aspect of the present disclosure, a method of etching a substrate includes: contacting a substrate having a thickness with an etchant arranged in a container for a period of time until the thickness is reduced by at least 2 μm at an average rate of 1 μm per minute to 6.7 μm per minute, the etchant having a temperature of 170° C. to 300° C. and comprising a molten mixture of two or more alkali metal hydroxides; and stopping contacting the substrate with the etchant.

[0006] According to a second aspect of the present disclosure, the method of the first aspect further comprises: before contacting the substrate with the etchant, increasing the texture of the surface of the substrate.

[0007] According to a third aspect of the present disclosure, the method of any one of the first to second aspects further comprises: before contacting the substrate with the etchant, increasing the texture of the surface of the substrate.

[0008] According to a fourth aspect of the present disclosure, in the method of the second aspect, increasing the texture of the surface of the substrate comprises sandblasting the surface.

[0009] According to a fifth aspect of the present disclosure, the method of the third aspect, wherein tempering the substrate comprises subjecting the substrate to an ion exchange procedure.

[0010] According to a sixth aspect of the present disclosure, in the method of any one of the first to fifth aspects, the etchant further comprises one or more of an alkali metal nitrate and an alkali metal sulfate.

[0011] According to a seventh aspect of the present disclosure, the method of the sixth aspect, wherein the alkali metal nitrate is one or more of KNO3 and NaNO3.

[0012] According to an eighth aspect of the present disclosure, the method of the sixth aspect, wherein the alkali metal sulfate is one or more of K2SO4 and Na2SO4.

[0013] According to a ninth aspect of the present disclosure, the method of the sixth aspect, wherein one or more of the alkali metal nitrate and the alkali metal sulfate is greater than 0 wt % (weight %) to 95 wt % of the etchant.

[0014] According to a tenth aspect of the present disclosure, in the method of any one of the first to fifth aspects, the etchant comprises a molten mixture of NaOH and KOH.

[0015] According to an eleventh aspect of the present disclosure, in the method of any one of the first to fifth aspects, the etchant comprises a molten mixture of 24 wt % to 72 wt % of NaOH and 76 wt % to 28 wt % of KOH.

[0016] According to a twelfth aspect of the present disclosure, in the method of any one of the first to eleventh aspects, the substrate is an alkali aluminosilicate glass substrate or an alkali aluminosilicate glass ceramic substrate.

[0017] According to a thirteenth aspect of the present disclosure, the method of any one of the first to twelfth aspects, wherein the time period is between 5 minutes and 2 hours.

[0018] According to a fourteenth aspect of the present disclosure, the method of any one of the first to thirteenth aspects, wherein the substrate has a composition; and the method makes Na in the composition from the surface to a depth of 1 μm in the thickness + , K + , Li + The weight percentage change of any one or more of the above is less than 5%.

[0019] According to a fifteenth aspect of the present disclosure, the method of any one of the first to thirteenth aspects, wherein the substrate has a composition; and the method makes Na in the composition at a depth of 1 μm from the surface to the thickness + , K + , Li + The weight percentage change of any one or more of the above is less than 1%.

[0020] According to a sixteenth aspect of the present disclosure, the method of any one of the first to fifteenth aspects, wherein the substrate has a composition; and the method makes Ca in the composition at a depth of 1 μm from the surface to the thickness ++ Mg ++ The weight percentage change of any one or more of the above is less than 5%.

[0021] According to a seventeenth aspect of the present disclosure, the method of any one of the first to fifteenth aspects, wherein the substrate has a composition; and the method makes Ca in the composition at a depth of 1 μm from the surface to the thickness ++ Mg ++ The weight percentage of any one or more of the above is changed by less than 1%.

[0022] According to the eighteenth aspect of the present disclosure, the method of the first aspect, wherein the substrate is one of a plurality of substrates, each substrate having a thickness, and the method further comprises: maintaining the etchant arranged in the container; for each remaining substrate of the plurality of substrates, sequentially: (a) contacting the substrate with the etchant placed in the container for a period of time until the thickness is reduced by at least 2 μm, and at an average rate of 1 μm per minute to 6.7 μm per minute; and (b) removing the substrate from contact with the etchant.

[0023] According to a nineteenth aspect of the present disclosure, the method of the eighteenth aspect, wherein the number of the plurality of substrates is at least 10 substrates.

[0024] According to a twentieth aspect of the present disclosure, the method of any one of aspects 18 to 19, wherein each of the plurality of substrates is formed from the same batch composition.

[0025] According to a twenty-first aspect of the present disclosure, the method of any one of aspects 18 to 20 further includes: before contacting each of the remaining substrates in the plurality of substrates, increasing the texture of the surface of each of the remaining substrates in the plurality of substrates.

[0026] According to a twenty-second aspect of the present disclosure, the method of any one of aspects 18 to 21 further includes: tempering each remaining substrate of the plurality of substrates via an ion exchange procedure.

[0027] According to the twenty-third aspect of the present disclosure, a system for reducing the thickness of a substrate includes: (a) a container; (b) an etchant placed in the container, the etchant contacts the surface of the container, the etchant comprises a molten mixture of two or more alkali metal hydroxides, and the temperature of the etchant is 170°C to 300°C; the substrate has a first position, a second position and a third position, in which the substrate is not in contact with the etchant in the first position, the substrate is in contact with the etchant in the second position, and the substrate is not in contact with the etchant again in the third position, and comprises a thickness, wherein the thickness at the first position is at least 2 μm greater than that at the third position, and at the second position, its thickness decreases at a rate of 1 μm to 6.7 μm per minute.

[0028] According to a twenty-fourth aspect of the present disclosure, in the twenty-third aspect, the surface of the container in contact with the etchant is polytetrafluoroethylene.

[0029] According to a twenty-fifth aspect of the present disclosure, in the twenty-third aspect, the surface of the container in contact with the etchant is nickel.

[0030] According to a twenty-sixth aspect of the present disclosure, in any one of aspects twenty-third to twenty-fifth, the etchant comprises a molten mixture of NaOH and KOH.

[0031] According to a twenty-seventh aspect of the present disclosure, in any one of aspects twenty-third to twenty-fifth, the etchant comprises a molten mixture of 24 wt % to 72 wt % of NaOH and 76 wt % to 28 wt % of KOH.

[0032] According to a twenty-eighth aspect of the present disclosure, in any one of aspects twenty-third to twenty-seven, the substrate is an alkali aluminosilicate glass substrate or an alkali aluminosilicate glass ceramic substrate.

[0033] According to a twenty-ninth aspect of the present disclosure, the system of any one of aspects twenty-third to twenty-eighth further includes: a heating element in communication with the etchant.

[0034] According to a thirtieth aspect of the present disclosure, in any one of the twenty-third to twenty-ninth aspects, the substrate has a region under compressive stress.

[0035] According to a thirty-first aspect of the present disclosure, in any one of aspects 23 to 30, the thickness of the substrate at the third position is at least 20 μm smaller than the thickness of the substrate at the first position.

[0036] According to a thirty-second aspect of the present disclosure, in any one of aspects twenty-third to thirty-first, the substrate is in the second position for a period of 10 minutes to 30 minutes.

[0037] According to a thirty-third aspect of the present disclosure, in any one of aspects 23 to 32, the etchant further comprises one or more of an alkali metal nitrate and an alkali metal sulfate.

[0038] According to the thirty-fourth aspect of the present disclosure, in any one of the twenty-third aspect to the thirty-third aspect, the substrate further comprises a composition and a first surface, the first surface contacts the etchant at the second position of the substrate, and when the substrate is at the third position, from the first surface to a depth of 1 μm in the thickness, Na in the substrate composition + , K + , Li + The weight percentage of any one or more of the above is the same as the weight percentage of Na in the composition of the substrate from the first surface to a depth of 1 μm in the thickness when the substrate is in the first position. + , K + , Li + The percentage of any one or more of the above differs by ±5%.

[0039] According to a thirty-fifth aspect of the present disclosure, in any one of aspects twenty-third to thirty-third, the substrate further comprises a composition and a first surface, the first surface contacts the etchant at the second position of the substrate, and when the substrate is at the third position, from the first surface to a depth of 1 μm in the thickness, Ca in the substrate composition is ++ Mg ++ The weight percentage of any one or more of the above is the same as the weight percentage of Ca in the substrate composition from the first surface to a depth of 1 μm in the thickness when the substrate is in the first position. ++ Mg ++ The percentage of any one or more of the above differs by ±5%.

[0040] According to the thirty-sixth aspect of the present disclosure, the system of the twenty-third aspect also includes: a plurality of substrates including the substrate, each of the plurality of substrates having a first position in which the substrate does not contact the etchant, a second position in which the substrate contacts the etchant, and a third position in which the substrate again does not contact the etchant, and the thickness of the first position is greater than the thickness of the third position, while the thickness of the second position decreases at a rate of 1 μm to 6.7 μm per minute.

[0041] Other features and advantages are given in the following detailed description, some of which are readily apparent to those skilled in the art from the description or recognized by practicing the various embodiments described herein, including the following detailed description, claims, and drawings.

[0042] It should be understood that the foregoing general description and the following detailed description are merely exemplary and are intended to provide an overall review or framework for understanding the nature and characteristics of the claims. The included drawings provide a further understanding and are incorporated into and constitute a part of this specification. The drawings illustrate one or more embodiments and, together with the description, are used to explain the principles and operation of the various embodiments.

[0043] Brief description of the attached figure

[0044] Figure 1 is a schematic diagram of a system including a container containing an etchant and a substrate of a plurality of substrates having a thickness and not in contact with the etchant in a first position.

[0045] Figure 2 Contains etchant Figure 1 a perspective view of a container showing a substrate in a second position in contact with an etchant, which reduces the thickness of the substrate;

[0046] Figure 3 yes Figure 1 Schematic diagram of a system showing a substrate in a third position that is no longer in contact with the etchant and in which a thickness of the substrate in the third position is reduced relative to a thickness of the substrate in the first position due to the etchant removing a portion of the substrate;

[0047] Figure 4 yes Figure 1 A front view of a substrate of a system of FIG. 1 showing a thickness at a third location after contact with an etchant and a thicker thickness of the substrate at a first location before contact with the etchant as indicated by a dashed line;

[0048] Figure 5 yes Figure 1an elevation view of a substrate of a system of the type shown having a compressive stress region adjoining a first surface and a second surface and having a tensile stress region between the compressive stress region, the compressive stress region and the tensile stress region being added according to the tempering step of the method disclosed herein;

[0049] Figure 6 It is etching Figure 1 A flow chart of a method of contacting a substrate with an etchant system, showing the steps of contacting the substrate with an etchant and stopping contacting the substrate with the etchant, and optional steps of texturing and tempering the substrate;

[0050] Figure 7 yes Figure 6 Schematic diagram of an optional texturing step of the method, showing that the texturing step increases Figure 1 protrusion of surface features at a textured surface of a substrate of the system;

[0051] Figure 8 is a diagram of Example 1 of the present disclosure, which shows Figure 6 A linear trend line after plotting the natural logarithm of the etching rate during a step of the method Figure 1 The linear trend line is a function of the inverse (multiplied by 1000) of the temperature of the etchant for a system in which the etchant contacts the substrate (according to the Arrhenius equation);

[0052] Fig. 9 is a diagram of Embodiment 1 of the present disclosure, which shows Figure 8 A graph of the equations generated by establishing trend lines, a graph of the calculated etch rate as a function of etchant temperature;

[0053] Fig.10 is a diagram related to Example 1 of the present disclosure, which shows Figure 6 before the method, the silicon-normalized relative abundances of lithium, phosphorus, and aluminum in the substrate as a function of depth from the first surface in the first position;

[0054] Fig.11 is a diagram related to Example 1 of the present disclosure, showing the process of contacting the substrate at the second position with the etchant and then stopping the contact. Figure 6 After the steps of the method, the silicon-normalized relative abundances of lithium, phosphorus, and aluminum in the substrate vary as a function of the depth from the first surface in the third position;

[0055] Fig.12 is a diagram related to Embodiment 2 of the present disclosure, which shows Figure 6and the temperature of the etchant in contact with the substrate, a decrease in thickness of the substrate in a third position relative to the first position after contacting the etchant in the second position, as a function of the particular sample of the example; and

[0056] Fig.13 is a Weibull plot for Example 4 of the present disclosure showing the improvement of the etching speed for a substrate subjected to a molten eutectic mixture of NaOH and KOH compared to a substrate etched by an aqueous solution. Figure 6 The percentage probability of substrate fracture as a function of the ring-on-ring load on the substrate for the different steps. DETAILED DESCRIPTION

[0057] Reference will now be made in detail to the preferred embodiments of the present disclosure, examples of which are illustrated in the accompanying drawings. Wherever possible, the same reference numerals will be used throughout the drawings to refer to the same or like parts.

[0058] I. System to reduce substrate thickness

[0059] Reference now Figures 1 to 5 , a system 10 for reducing a thickness 12 of a substrate 14a is shown. The system 10 includes a container 16, an etchant 18, and a substrate 14a. The container 16 includes at least one sidewall 20 forming a cavity 22 and an opening 24 leading to the cavity 22. The container 16 has a surface 26 open to the cavity 22, for example, at the at least one sidewall 20. The etchant 18 is disposed in the cavity 22 of the container 16. The surface 26 of the container 16 thus contacts the etchant 18 disposed within the container 16. The substrate 14a has a first position 28 ( Figure 1 )、Second position 30( Figure 2 ) and the third position 32( Figure 3 ). In the first position 28 ( Figure 1 ), the substrate 14a does not contact the etchant 18. At the second position 30 ( Figure 2 ), the substrate 14a contacts the etchant 18. In an embodiment, the substrate 14a contacts the etchant 18 by immersing, dipping, immersing, or otherwise placing a portion or all of the substrate 14a in the etchant 18 disposed in the container 16. At the third position 32 ( Figure 3 ), substrate 14a is again not in contact with etchant 18. However, substrate 14a has a thickness 12, which includes thickness 12a at first position 28, which is at least 2 μm greater than thickness 12b at third position 32. Thickness 12 of substrate 14a decreases from thickness 12a to thickness 12b at second position 30 at a rate of 1 μm per minute to 6.7 μm per minute.

[0060] The etchant 18 includes a molten mixture of two or more alkali metal hydroxides. In an embodiment, the etchant 18 is or includes a eutectic molten mixture of two alkali metal hydroxides. In an embodiment, the etchant 18 is or includes a eutectic molten mixture of NaOH and potassium hydroxide (KOH). The mixture of molten NaOH and KOH is eutectic, which allows the mixture to completely melt at a temperature lower than the temperature at which pure NaOH or pure KOH would melt. For example, a mixture of 43.1wt% NaOH and 56.9wt% KOH will completely melt at above 174.5°C, while pure KOH becomes molten at above 400°C, and pure NaOH becomes molten at above 300°C. Suitable mixtures include 24wt% to 72wt% NaOH, and the remainder (76wt% to 28wt%) KOH. As a molten mixture, water is not intentionally included.

[0061] The etchant 18 comprising an alkali metal hydroxide may corrode the surface 26 of the container 16. The extent of the corrosion depends on the composition of the surface 26 of the container 16 and the temperature of the etchant 18. In an embodiment, the surface 26 is polytetrafluoroethylene (e.g., Teflon, distributed by Chemours, Inc., Wilmington, Delaware, USA). At temperatures below 250° C., molten sodium hydroxide (NaOH), an alkali metal hydroxide, does not pose a significant risk of corrosion to polytetrafluoroethylene. Therefore, in an embodiment, the etchant 18 is or comprises a molten mixture of NaOH and at least one other alkali metal hydroxide, the surface 26 of the container 16 is polytetrafluoroethylene, and the temperature of the etchant 18 is below 250° C.

[0062] In other embodiments, surface 26 is or comprises nickel. At temperatures below 300° C., molten sodium hydroxide (NaOH) does not pose a significant corrosion risk to nickel. Therefore, in embodiments, etchant 18 is or comprises a molten mixture of NaOH and at least one other alkali metal hydroxide, surface 26 of container 16 is or comprises nickel, and the temperature of etchant 18 is below 300° C.

[0063] In an embodiment, the temperature of the etchant 18 is 170°C to 300°C, for example, 170°C to 250°C. As described above, exceeding the upper limit of 300°C may damage the surface 26 of the container 16, even if the surface 26 is nickel or contains nickel. Exceeding the upper limit of 250°C may damage the surface 26 of the container 16, even when the surface 26 is polytetrafluoroethylene. In addition, as discussed further below, for substrates 14a of certain compositions, when the temperature of the etchant 18 exceeds 300°C or 250°C, the etchant 18 etches the substrate 14a too quickly to be adequately controlled. When the temperature of the etchant 18 is below the lower limit of 170°C, the temperature may not be sufficient to keep the mixture of alkali metal hydroxides in a molten state, and the speed at which the etchant 18 etches the substrate 14a is too slow to be commercially practical, which is one of the problems that the present disclosure intends to solve.

[0064] In an embodiment, the system 10 further includes a heating element 34. The heating element 34 is in communication with the etchant 18. The heating element 34 raises the temperature of the etchant 18 to a desired temperature of 170°C to 300°C and maintains the etchant 18 at that temperature.

[0065] In an embodiment, the substrate 14a is a sheet having two major surfaces (a first surface 36a and a second surface 36b) that face substantially opposite directions and are substantially coplanar. The thickness 12 is the linear distance between the first surface 36a and the second surface 36b. In an embodiment, the thickness 12a before contacting the substrate 14a with the etchant 18 is less than 5 mm. In an embodiment, the thickness 12a is in the range of 250 μm to 5 mm, 250 μm to 3 mm, 250 μm to 1 mm, or 500 μm to 1 mm. In an embodiment, the thickness 12b of the substrate 14a at the third position 32 is at least 2 μm smaller than the thickness 12a at the first position 28. In other embodiments, the thickness 12b at the third position 32 is at least 10 μm, or at least 20 μm, or at least 50 μm, or at least 100 μm, or at least 200 μm, or at least 300 μm smaller than the thickness 12a at the first position 28. In other embodiments, the thickness 12b at the third location 32 is 98.5% or less (or 94% or less, or 60% or less) of the thickness 12a at the first location 28. In other embodiments, the thickness 12b at the third location 32 is between 50% and 98.5% of the thickness 12a at the first location 28.

[0066] The thickness 12a of the substrate 14a at the first position 28 (i.e., before contacting the etchant 18) can be measured using a micrometer. To determine the thickness 12b of the substrate 14 in the third position 32 (i.e., after step 46 of contacting the etchant 18), the mass of the substrate 14a in the first position 28 is compared to the mass of the substrate 14a in the third position 32. The decrease in thickness 12a of the substrate 14a during step 46 is proportional to the decrease in mass of the substrate 14a during step 46. For example, if the thickness 12a of the substrate 14a at the first position 28 is 1 mm ("initial thickness"), and the mass of the substrate 14a at the first position 28 is 10 grams ("initial mass"), and the mass of the substrate 14a at the third position 32 is 9 grams ("final mass"), then in step 46, the decrease in thickness 12 ("Δ thickness") is calculated to be 100 μm (0.1 mm) according to equation (1) below:

[0067]

[0068] The thickness 12b ("final thickness") of the substrate 14b at the third position 32 is calculated to be 0.9 mm according to the following equation (2):

[0069] Final thickness = initial thickness - Δthickness

[0070] According to equation (3) below, the rate at which thickness 12 decreases during step 46 (the "etch rate") is calculated as:

[0071]

[0072] Therefore, continuing this example, if the etching time of step 46 is 1 hour, the etching rate is 0.1mm / 1hr=0.1mm / hr or 100μm / hr. Step 46 can result in a change in the thickness 12b of the substrate 14a. Therefore, after step 46, the thickness 12b of the substrate 14a at the third position 32 is calculated as a function of the mass change of the substrate 14a, and this calculation provides a more accurate determination of the thickness 12b in the third position 32. Compared with the non-main surface (e.g., the exposed side surface) of the contact etchant 18, the larger the surface area of ​​the first surface 36a and the second surface 36b of the contact etchant 18, the higher the accuracy of determining the thickness 12b by using the measured mass change of the substrate 14.

[0073] As described above, when the etchant 18 is in contact with the second position 30, the rate at which the etchant 18 reduces the thickness 12 of the substrate 14a is controlled to be 1 μm to 6.7 μm per minute (i.e., 60 μm per hour to 400 μm per hour). The rate at which the etchant 18 reduces the thickness 12 of the substrate 14a is a function of the temperature of the etchant 18 - the higher the temperature, the faster the rate. This concept will be further explained below. In an embodiment, the rate of 1 μm per minute to 6.7 μm per minute is the average rate for the entire period of time that the substrate 14a is in contact with the etchant 18 at the second position 30. In an embodiment, when the substrate 14a is a sheet having a first surface 36a and a second surface 36b and the first surface 36a and the second surface 36b are both in contact with the etchant 18 at the second position 30, a rate of 1 μm per minute to 6.7 μm per minute is applicable.

[0074] In an embodiment, the film covers either the first surface 36a or the second surface 36b such that when in the second position 30, the covered first surface 36a or the second surface 36b cannot be contacted by the etchant 18. In such an embodiment, the etchant 18 reduces the thickness 12 of the substrate 14a at a rate of 0.5 μm per minute to 3.35 μm per minute (i.e., 30 μm per hour to 200 μm per hour).

[0075] Above a rate of 6.7 μm per minute, the etchant 18 reduces the thickness 12b of the substrate 14a too quickly to ensure that the thickness 12b of the substrate 14a at the third location 32 is within an acceptable tolerance range. A rate of 1.0 μm per minute when both surfaces 36a, 36b of the substrate 14a contact the etchant 18 (or a rate of 0.5 μm when only one of the surfaces 36a, 36b contact the etchant 18) ensures that migration (e.g., ion exchange) from the etchant 18 does not substantially change the composition of the substrate 14a at the contacting surfaces 36a, 36b. In other words, if the etching rate is less than 1 μm per minute (or 0.5 μm per minute as the case may be), ion exchange between the etchant 18 and the substrate 14a may substantially change the composition of the substrate 14a at the surface in contact with the etchant 18. The etchant 18 includes alkali metal ions. In an embodiment, the substrate 14a includes alkali metal ions (e.g., Na + , K + , Li + ) and / or alkaline earth metal ions (e.g., Mg ++ , Ca ++). At the second location 30, the surfaces 36a, 36b of the substrate 14a that are in contact with the etchant 18 at any given point in time are etched away faster than ions can migrate into or out of the substrate 14a. If this were not the case, and the composition of the substrate 14a at the exposed surfaces 36a, 36b could change substantially, any subsequent chemical tempering of the substrate 14a that may be performed would be adversely affected. Furthermore, the substantial change in the composition of the substrate 14a at the exposed surfaces 36a, 36b could cause the substrate 14a to warp.

[0076] In an embodiment, a first surface 36a of the substrate 14a contacts the etchant 18 at a second location 30 of the substrate 14a, and the composition of the substrate 14a is substantially the same from the first surface 36a to a depth of 1 μm in the thickness 12 at the first location 28 and at the third location 32. In an embodiment, a second surface 36b of the substrate 14a contacts the etchant 18 at the second location 30 of the substrate 14a, and the composition of the substrate 14a is substantially the same from the second surface 36b to a depth of 1 μm in the thickness 12 at the first location 28 and at the third location 32.

[0077] In an embodiment, first surface 36a of substrate 14a contacts etchant 18 at second position 30 of substrate 14a, and Na in the composition of substrate 14a from first surface 36a to a depth of 1 μm in thickness 12b when substrate 14a is in third position 32 is less than 1 μm. + , K + , Li + The weight percentage of any one or more of the above is the same as the Na in the composition of the substrate 14a from the first surface 36a to a depth of 1 μm in the thickness 12a when the substrate 14a is in the first position 28. + , K + , Li + For example, assuming that in a first location 28 of substrate 14a, Li + The concentration of Li in the composition of the substrate 14a is 1.5 wt % in the third position 32 of the substrate 14a. Then, in the composition of the substrate 14a from the first surface 36a to a depth of 1 μm in the thickness 12b, Li + The concentration of Na in the composition of substrate 14a from first surface 36a to a depth of 1 μm in thickness 12b is not more than 1.575 wt% (1.05×1.5) and not less than 1.425 wt% (0.95×1.5). In an embodiment, first surface 36a of substrate 14a contacts etchant 18 at second position 30 of substrate 14a, and when substrate 14a is in third position 32, Na in the composition of substrate 14a from first surface 36a to a depth of 1 μm in thickness 12b is not less than 1.575 wt% (1.05×1.5) and not less than 1.425 wt% (0.95×1.5). +, K + , Li + The weight percentage of any one or more of the above is the same as the Na in the composition of the substrate 14a from the first surface 36a to a depth of 1 μm in the thickness 12a when the substrate 14a is in the first position 28. + , K + , Li + The weight percentage of any one or more of the above mentioned components differs by ±1%.

[0078] In an embodiment, first surface 36a of substrate 14a contacts etchant 18 at second position 30 of substrate 14a, and Ca in the composition of substrate 14a from first surface 36a to a depth of 1 μm in thickness 12b when substrate 14a is in third position 32 is less than 1 μm. ++ Mg ++ The weight percentage of any one or more of the above is the same as the weight percentage of Ca in the composition of the substrate 14a from the first surface 36a to a depth of 1 μm in the thickness 12a when the substrate 14a is in the first position 28. ++ Mg ++ For example, assuming that in a first location 28 of substrate 14a, Ca in the composition of substrate 14a from first surface 36a to a depth of 1 μm in thickness 12a is ++ The concentration is 1.5 wt % of the composition of the substrate 14a. Then, in the third position 32 of the substrate 14a, the Ca content in the composition of the substrate 14a from the first surface 36a to a depth of 1 μm in the thickness 12b is ++ The concentration of Ca in the composition of substrate 14a from first surface 36a to a depth of 1 μm in thickness 12b is not more than 1.575 wt% (1.05×1.5) and not less than 1.425 wt% (0.95×1.5). In an embodiment, first surface 36a of substrate 14a contacts etchant 18 at second position 30 of substrate 14a, and when substrate 14a is in third position 32, Ca in the composition of substrate 14a from first surface 36a to a depth of 1 μm in thickness 12b is not less than 1.575 wt% (1.05×1.5) and not less than 1.425 wt% (0.95×1.5). ++ Mg ++ The weight percentage of any one or more of the above is the same as the weight percentage of Ca in the composition of the substrate 14a from the first surface 36a to a depth of 1 μm in the thickness 12a when the substrate 14a is in the first position 28. ++ Mg ++ The weight percentage of any one or more of the above mentioned components differs by ±1%.

[0079] Depending on the desired thickness 12b of the substrate 14a at the third position 32, the temperature of the etchant 18, and the composition of the substrate 14a, the substrate 14a is in contact with the etchant 18 for a period of time ranging from 5 minutes to 2 hours while in the second position 30. In an embodiment, the substrate 14a is in contact with the etchant 18 for a period of time ranging from 10 minutes to 30 minutes in the second position 30.

[0080] Substrate 14a can be a glass substrate or a glass ceramic substrate. Glass substrate or glass ceramic substrate can have the composition of soda lime glass or glass ceramic, alkali aluminosilicate glass or glass ceramic, borosilicate glass or glass ceramic containing alkali metal and alkali aluminoborosilicate glass or glass ceramic, but other glass compositions are also considered. In an embodiment, substrate 14a is an alkali aluminosilicate glass substrate or an alkali aluminosilicate glass ceramic substrate. Such glass or glass ceramic composition can be chemically enhanced by an ion exchange process. In some variations, the composition can be free of lithium ions. Various methods can be used to form substrate 14a, such as float glass process and down-drawing process, such as fusion drawing and slot drawing.

[0081] In an embodiment, the substrate 14a has been tempered (i.e., strengthened) to have a region 38a under compressive stress ("CS") and adjacent to the first surface 36a and a region 38b adjacent to the second surface 36b. Contacting the substrate 14a with the etchant 18 in the second position 30 can be used to remove surface defects that are generated when the regions 38a, 38b under compressive stress (e.g., by ion exchange) are generated, thereby further improving the strength of the substrate 14a. The regions 38a, 38b under compressive stress extend from the first surface 36a and / or the second surface 36b to compression depths 40a, 40b, respectively. The generation of compressive stress further generates a central region 42 under tensile stress, with a maximum value at the center of the central region 42, referred to as central tension or central tension (CT). The central region 42 extends between the compression depths 40a, 40b and is under tensile stress. The tensile stress of the central region 42 balances the compressive stress of the regions 38a, 38b under compressive stress. As used herein, the terms "depth of compression" and "DOC" refer to the depth at which the stress within the substrate 14a changes from compressive stress to tensile stress. At the compression depth 40a, 40b, the stress crosses from positive (compressive) stress to negative (tensile) stress and thus has a value of zero. In an embodiment, the compression depths 40a, 40b are each at least 20 μm. In an embodiment, the absolute value of the maximum compressive stress CS within the regions 38a, 38b is at least 200 MPa, at least about 400 MPa, at least 600 MPa, or up to about 1000 MPa.

[0082] Douglas Clippinger Allan et al. disclose two methods for extracting detailed and accurate stress distribution (stress as a function of depth) of a substrate 14a having regions 38a, 38b under compressive stress in U.S. Patent No. 9,140,543, entitled “Systems and Methods for Measuring the Stress Profile of Ion-Exchanged Glass,” filed on May 3, 2012, which claims priority to U.S. Provisional Patent Application No. 61 / 489,800 with the same title filed on May 25, 2011, the entire contents of which are incorporated herein by reference.

[0083] The alkali aluminosilicate glass composition suitable for substrate 14a comprises aluminum oxide, at least one alkali metal, and in some embodiments, greater than 50 mol % (mol %) SiO2, in other embodiments at least 58 mol % SiO2, and in other embodiments at least 60 mol % SiO2, wherein (Al2O3+B2O3) / Σ 改性剂 The ratio of (i.e., the sum of the modifiers) is greater than 1, wherein the ratio of the components is expressed in mol% and the modifier is an alkali metal oxide. In a specific embodiment, the composition comprises: 58-72 mol% SiO2; 9-17 mol% Al2O3; 2-12 mol% B2O3; 8-16 mol% Na2O; and 0-4 mol% K2O, wherein (Al2O3+B2O3) / Σ 改性剂 (ie, the sum of the modifiers) is greater than 1.

[0084] Another suitable alkali aluminosilicate glass composition for substrate 14a comprises: 64-68 mol% SiO2; 12-16 mol% Na2O; 8-12 mol% Al2O3; 0-3 mol% B2O3; 2-5 mol% K2O; 4-6 mol% MgO; and 0-5 mol% CaO, wherein: 66 mol%≦SiO2+B2O3+CaO≦69 mol%; Na2O+K2O+B2O3+MgO+CaO+SrO>10 mol%; 5 mol%≦MgO+CaO+SrO≦8 mol%; (Na2O+B2O3)–Al2O3≦2 mol%; 2 mol%≦Na2O-Al2O3≦6 mol%; and 4 mol%≦(Na2O+K2O)-Al2O3≦10 mol%.

[0085] Another suitable alkali aluminosilicate glass composition for substrate 14a comprises: 2 mol % or more of Al2O3 and / or ZrO2, or 4 mol % or more of Al2O3 and / or ZrO2.

[0086] An exemplary glass composition comprises SiO2, B2O3 and Na2O, wherein (SiO2+B2O3)≧66mol% and Na2O≧9mol%. In one embodiment, the composition comprises at least 6wt% alumina. In another embodiment, the composition of one or more alkaline earth metal oxides, such as the content of alkaline earth oxides, is at least 5wt%. In some embodiments, the suitable composition further comprises at least one of K2O, MgO and CaO. In a particular embodiment, the composition of the substrate 14a is 61-75mol% SiO2; 7-15mol% Al2O3; 0-12mol% B2O3; 9-21mol% Na2O; 0-4mol% K2O; 0-7mol% MgO and 0-3mol% CaO.

[0087] Another example composition suitable for substrate 14a includes: 60-70 mol% SiO2; 6-14 mol% Al2O3; 0-15 mol% B2O3; 0-15 mol% Li2O; 0-20 mol% Na2O; 0-10 mol% K2O; 0-8 mol MaO; 0-10 mol% CaO; 0-5 mol% ZrO2; 0-1 mol% SnO2; 0-1 mol% CeO2; less than 50 ppm As2O3; and less than 50 ppm Sb2O3; wherein 12 mol%≦(Li2O+Na2O+K2O)≦20 mol% and 0 mol%≦(MgO+CaO)≦10 mol%.

[0088] Another example glass composition suitable for substrate 14a includes: 63.5-66.5 mol% SiO2; 8-12 mol% Al2O3; 0-3 mol% B2O3; 0-5 mol% Li2O; 8-18 mol% Na2O; 0-5 mol% K2O; 1-7 mol% MgO; 0-2.5 mol% CaO; 0-3 mol% ZrO2; 0.05-0.25 mol% SnO2; 0.05-0.5 mol% CeO2; less than 50 ppm As2O3; and less than 50 ppm Sb2O3; wherein 14 mol%≦(Li2O+Na2O+K2O)≦18 mol% and 2 mol%≦(MgO+CaO)≦7 mol%.

[0089] Substrate 14a can be a ceramicized form of the above-mentioned glass composition. Substrate 14a can be an alkali aluminosilicate glass ceramic in addition to other options. In an embodiment, substrate 14a is a glass ceramic described in U.S. Patent Nos. 9,809,488 and 10,189,741 and U.S. Patent Application Publication No. 2016 / 0102010A1, all of which are incorporated herein by reference in their entirety. Exemplary glass ceramics suitable for substrate 14a include (in wt%): SiO2: 55-80%; Al2O3: 2-20%; Li2O: 5-20%; B2O3: 0-10%; Na2O: 0-5%; ZnO: 0-10%; P2O5: 0.5-6%; and ZrO2: 0.2-15%. The composition may include the following optional additional compositions (in wt%): K2O: 0-4%; MgO: 0-8%; TiO2: 0-5%; CeO2: 0-0.4% and SnO2: 0.05-0.5%. Another example glass ceramic suitable for substrate 14a includes (in wt%): SiO2: 69-80%; Al2O3: 6-9%; Li2O: 10-14%; B2O3: 0-2%; P2O5: 1.5-2.5%; ZrO2: 2-4%. Another example glass ceramic suitable for substrate 14a includes (in wt%): SiO2: 69-80%; Al2O3: 6-9%; Li2O: 10-14%; Na2O: 1-2%; K2O: 1-2%; B2O3: 0-12%; P2O5: 1.5-2.5%; and ZrO2: 2-4%. Another example glass ceramic suitable for substrate 14a includes (in wt%): SiO2: 65-80%; Al2O3: 5-16%; Li2O: 8-15%; Na2O: 0-3%; K2O: 0-3%; B2O3: 0-6%; ZnO: 0-2%; P2O5: 0.5-4%; and ZrO2: 0.2-6%. Another example glass-ceramic suitable for substrate 14a includes (in wt%): SiO2: 60-80%; Al2O3: 5-20%; Li2O: 5-20%; Na2O: 0-3%; K2O: 0-3%; B2O3: 0-6%; ZnO: 0-4%; P2O5: 0.5-4%; and ZrO2: 0.2-8%. In some embodiments, the sum of the weight percentages of P2O5 and ZrO2 in the glass-ceramic composition of substrate 14a is greater than 3. In some embodiments, the glass-ceramic has a petalite crystalline phase and a lithium silicate crystalline phase.

[0090] In an embodiment, the etchant 18 further includes one or more of an alkali nitrate and an alkali sulfate. For example, the alkali nitrate may be one or more of KNO3 and NaNO3, and the alkali sulfate may be one or more of K2SO4 and Na2SO4. If included in the etchant 18, the one or more of the alkali nitrate and the alkali sulfate may comprise 0 wt% to 95 wt% of the etchant 18. If the composition of the substrate 14a is such that contact with a pure molten mixture of two or more alkali hydroxides would reduce the thickness 12 of the substrate 14a too quickly, then the inclusion of one or more of the alkali nitrate and the alkali sulfate helps control the rate at which the etchant 18 reduces the thickness 12 of the substrate 14a to within a range of 1 μm per minute to 6.7 μm per minute.

[0091] In an embodiment, the system 10 further includes a plurality of substrates 14a, 14b ... 14n, of which the substrate 14a is one of them. Each of the plurality of substrates 14a, 14b ... 14n has a first position 28, a second position 30, and a third position 32, wherein the substrates 14a, 14b ... 14n are not in contact with the etchant 18 at the first position 28, the substrates 14a, 14b ... 14n are in contact with the etchant 18 at the second position 30, and the substrates 14a, 14b ... 14n are again not in contact with the etchant 18 at the third position 32. The thickness 12a of each of the plurality of substrates 14a, 14b ... 14n at the first position 28 is at least 2 μm greater than the thickness 12b at the third position 32. The thickness 12 of each of the plurality of substrates 14a, 14b ... 14n decreases at a rate of 1 μm to 6.7 μm when in the second position 30. The etchant 18 of the system 10 remains the same for all of the plurality of substrates 14a, 14b ... 14n, and the same etchant 18 reduces the thickness 12 of all of the plurality of substrates 14a, 14b ... 14n without replacing the etchant 18. The etchant 18 comprising a molten mixture of two or more alkali metal hydroxides remains effective for etching over a surprising number of cycles. In other words, the etchant 18 is able to continuously etch all of the plurality of substrates 14a, 14b ... 14n at approximately the same rate. In other words, the etching ability of the etchant 18 does not appear to decay rapidly. In an embodiment, the number of the plurality of substrates 14a, 14b ... 14n is at least ten (10).

[0092] II. Method 44 for Etching Substrate 14a

[0093] Reference now Figure 6 and Figure 7, a method 44 for etching a substrate 14a is described herein. In step 46, the method 44 includes contacting the substrate 14a with an etchant 18 disposed in a container 16 for a period of time until the thickness 12 is reduced by at least 2 μm. As described above, the temperature of the etchant 18 is 170° C. to 300° C. and includes or is a molten mixture of two or more alkali metal hydroxides. In order to contact the substrate 14a with the etchant 18, the substrate 14a moves from a first position 28 that is not in contact with the etchant 18 to a second position 30 that is in contact with the etchant 18. In an embodiment, the etchant 18 is or includes a molten mixture of NaOH and KOH. In an embodiment, the etchant 18 includes a molten mixture of 24 wt % to 72 wt % NaOH and 76 wt % to 28 wt % KOH. As described above, the etchant 18 may further include one or more of an alkali metal nitrate (e.g., KNO3, NaNO3) and an alkali metal sulfate (K2SO4, Na2SO4). In an embodiment, one or more of the alkali metal nitrate and the alkali metal sulfate accounts for greater than 0 wt % to 95 wt % of the etchant 18. The substrate 14a can be as described above, such as an alkali aluminosilicate glass substrate or an alkali aluminosilicate glass ceramic substrate. The time period can be as described above, such as between 5 minutes and 2 hours.

[0094] In step 48, method 44 also includes stopping contact between substrate 14a and etchant 18. That is, substrate 14a is moved from second position 30 to third position 32. Stopping contact between substrate 14a and etchant 18 stops etchant 18 from reducing thickness 12 of substrate 14a. To stop contact between substrate 14a and etchant 18, substrate 14a can be removed from container 16 containing etchant 18 and then rinsed with water, such as deionized water (e.g., Type I water with a resistance of 18.2 MΩ-cm). As described above, steps 46, 48 of method 44 change the composition of Na in the first surface 36a, the second surface 36b, or both the first surface 36a and the second surface 36b (depending on which surfaces contact etchant 18) to a depth of 1 μm in thickness 12. + , K + , Li + The weight percentage of any one or more of the above is less than 5%. In an embodiment, steps 46 and 48 of method 44 are such that the composition of Na + , K + , Li + As described above, steps 46, 48 of method 44 change the weight percentage of any one or more of Ca in the composition from the first surface 36a, the second surface 36b, or both the first surface 36a and the second surface 36b (depending on which surface contacts the etchant 18) to a depth of 1 μm in the thickness 12. ++ Mg ++The weight percentage of any one or more of the above is less than 5%. In an embodiment, steps 46 and 48 of method 44 provide that the composition of Ca ++ Mg ++ The weight percentage of any one or more of the changes is less than 1%.

[0095] In an embodiment, the method 44 further includes increasing the texture of the first surface 36a, the second surface 36b, or both the first surface 36a and the second surface 36b of the substrate 14a at step 50. Step 50 occurs before step 46 of contacting the substrate 14a with the etchant 18. The texturing of the first surface 36a forms a more obvious surface feature 52 at the first surface 36a, which has peaks 54 and valleys 56. Various measurements of "surface roughness" can quantify the increase in texture from step 50. For example, the arithmetic mean roughness value (Ra) is the arithmetic mean of the absolute value of the deviation 58 from the mean value line 60 of the measured roughness profile. The higher the Ra value, the greater the texture. Surface roughness quantification is typically performed using an atomic force microscope, such as an atomic force microscope controlled by a NanoNavi control station distributed by SeikoInstruments Inc. (Seiko Electronics Corporation, Chiba City, Japan). In an embodiment, the step 50 of increasing the texture of the surfaces 36a, 36b includes sandblasting the surfaces 36a, 36b. In the sandblasting process, sand is blasted on the surface 36a, 36b of the substrate 14a, and the diameter of the sand particles and the blasting pressure are controlled. For example, 220 grit SiC particles with an average diameter of 63 μm can be used for sandblasting at an air pressure of 60 psi. Other particles of different sizes can be sandblasted at different air pressures.

[0096] In an embodiment, the method 44 further includes tempering the substrate 14a in step 62. In an embodiment, the step 62 of tempering the substrate 14a is performed after the step 46 of contacting the substrate 14a with the etchant 18 and the step 48 of terminating the contact of the substrate 14a with the etchant 18. In other embodiments, the step 62 of tempering the substrate 14a is performed before the step 46 of contacting the substrate 14a with the etchant 18. As described above, tempering the substrate 14a produces the region 38a adjacent to the first surface 36a and the region 38b adjacent to the second surface 36b under compressive stress ("CS"). The step 62 of tempering the substrate 14a can be performed by a thermal tempering process or a chemical tempering process, or both.

[0097] In an embodiment, the step of tempering 62 is performed by an ion exchange chemical tempering process. In ion exchange, ions at or near the first surface 36a and the second surface 36b of the substrate 14a are replaced or exchanged with larger ions, generally having the same valence or oxidation state. In embodiments where the substrate 14a comprises, consists essentially of, or consists of an alkali aluminosilicate glass or glass ceramic, an alkali borosilicate glass or glass ceramic, an alkali aluminoborosilicate glass or glass ceramic, or an alkali silicate glass or glass ceramic, the ions in the surface layer of the glass or glass ceramic and the larger ions are monovalent alkali metal cations, such as Na + (When Li + ), K + , Rb + and Cs + Alternatively, the monovalent cations in, at, or near the first surface 36a and the second surface 36b may be replaced with monovalent cations other than alkali metal cations, such as Ag. + wait.

[0098] In an embodiment, the ion exchange process is performed by immersing the substrate 14a in a molten salt bath containing larger ions to be exchanged with smaller ions in the substrate 14a. It will be understood by those skilled in the art that the parameters of the ion exchange process include, but are not limited to, bath composition and temperature, immersion time, the number of immersions of the substrate 14a in one or more salt baths, the use of multiple salt baths, and additional steps such as annealing, washing, etc., which are generally determined by the composition of the substrate 14a and the desired compression depth 40a, 40b and the compressive stress of the substrate 14a generated by the tempering operation. For example, ion exchange of an alkali-containing glass or glass-ceramic substrate can be achieved by immersing it in at least one molten bath containing salts such as, but not limited to, nitrates, sulfates, and chlorides of larger alkali metal ions. In an embodiment, the molten salt bath contains potassium nitrate (0-100 wt%), sodium nitrate (0-100 wt%), and lithium nitrate (0-12 wt%), and the combination of potassium nitrate and sodium nitrate has a weight percentage in the range of 88 wt% to 100 wt%. In an embodiment, the temperature of the molten salt bath is generally from about 350°C to as high as about 500°C, and the immersion time is from about 15 minutes to as high as about 40 hours, including from about 20 minutes to about 10 hours. However, temperatures and immersion times different from those described above may also be used. The substrate 14a may be acid polished or otherwise treated to remove or reduce the effects of defects introduced at the first surface 36a and the second surface 36b during step 62.

[0099] In an embodiment, the substrate 14a is one of a plurality of substrates 14a, 14b, ... 14n, and each remaining substrate 14b, ... 14n of the plurality of substrates 14a, 14b, ... 14n has a thickness 12. In such an embodiment, at step 64, the method 44 further includes maintaining the etchant 18 disposed in the container 16, and then sequentially repeating steps 46, 48 (and optionally, steps 50, 62) for each remaining substrate 14b ... 14n of the plurality of substrates 14a, 14b, ... 14n. In other words, for each remaining substrate 14b ... 14n of the plurality of substrates 14a, 14b, ... 14n, the method 44 further includes performing: (a) step 46, contacting the substrate 14n with the etchant 18 disposed in the container 16 for a period of time until the thickness 12 is reduced by at least 2 μm and at an average rate of 1 μm per minute to 6.7 μm per minute; and (b) step 48, stopping contacting the substrate 14n with the etchant 18. In an embodiment, the period of time that the substrate 14n is in contact with the etchant 18 during step 46 is the same for each substrate 14n in the plurality of substrates 14a, 14b, ... 14n. In an embodiment, the number of the plurality of substrates 14a, 14b, ... 14n is at least 10. As mentioned above and further described below, the etchant 18 has been experimentally shown to be capable of sequentially etching a relatively high number of the plurality of substrates 14a, 14b, ... 14n at an acceptable rate.

[0100] In an embodiment, each substrate in the plurality of substrates 14a, 14b, ... 14n is formed from the same batch composition, and thus each substrate 14n has substantially the same composition. In an embodiment, the method 44 further comprises increasing the texture of the surface 36a, 36b of each remaining substrate 14n in the plurality of substrates 14a, 14b, ... 14n, i.e., performing step 50 on each remaining substrate 14b in the plurality of substrates 14a, 14b, ... 14n. In an embodiment, the method 44 further comprises tempering each remaining substrate 14n in the plurality of substrates 14a, 14b, ... 14n, i.e., performing step 62 on each remaining substrate 14n in the plurality of substrates 14a, 14b, ... 14n.

[0101] III. Embodiment

[0102] Example 1: In Example 1, three 50 mm×50 mm samples (Samples 1-3) of a glass ceramic substrate were prepared. The sample of substrate 14a had a thickness 12a at the first position 28 (before step 46 of method 44), as shown in Table 1 below. The thickness 12 of substrate 14a at the first position 28 was measured with a micrometer and is represented as initial thickness 12a in Table 1 below. The mass of each sample was measured with a balance and is represented as "initial mass" in Table 1 below. Then, according to step 46 of method 44, the samples of substrate 14a were each individually placed in the second position 30 in sequence and contacted with etchant 18. Both the first surface 36a and the second surface 36b of the sample of substrate 14a contacted etchant 18. Etchant 18 is a molten mixture of two alkali metal hydroxides. Specifically, etchant 18 is a molten mixture of 43 wt% NaOH and 57 wt% KOH. The melting point (becoming molten) of the molten mixture is higher than about 175°C. Each of the three samples of substrate 14a was contacted with etchant 18 for a different period of time at a different etchant 18 temperature: for sample 1, contact was made at 300°C for 10 minutes; sample 2 was contacted at 245°C for 5 minutes; and sample 3 was contacted at 225°C for 43 minutes. Then, according to step 48 of method 44, each sample was placed in a third position 32 to stop contact with etchant 18. The mass of each sample was then measured using a balance and is represented as "final mass" in Table 1 below. The difference between the initial mass and the final mass (initial mass - final mass) is represented as "Δ". According to equations (1) and (2) above, the thickness 12b of each sample at the third position 32 (i.e., no longer contacting etchant 18) was calculated to be proportional to the change in mass and is represented as "final thickness 12b" in Table 1 below.

[0103] Different combinations of the temperature of the etchant 18 and the time period that the substrate 14a is in contact with the etchant 18 cause the etchant 18 to reduce the thickness 12 of the corresponding samples at different average etching rates: Sample 1 has an average etching rate of 2150.2 μm per hour (35.8 μm per minute); Sample 2 has an average etching rate of 174.5 μm per hour (2.91 μm per minute); and Sample 3 has an average etching rate of 75.0 μm per hour (1.25 μm per minute). These etching rates are calculated according to equation (3) above. The results show that the increased temperature provides an increased average etching rate. Sample 1 with an etchant 18 at 300°C provides an etching rate of 35.8 μm per minute (i.e., more than 0.5 μm per second), which is much greater than the maximum value of about 6.7 μm per minute to continuously provide the substrate 14a with a predetermined thickness 12b at the third position 32 within an acceptable tolerance range. The temperature of 245°C for sample 2 and 225°C for sample 3 resulted in a controllable etching rate with an average rate ranging from 1 μm to 6.7 μm per minute (i.e., 60 μm to 400 μm per hour), specifically 174.5 μm per hour (2.9 μm per minute) and 75.0 μm per hour (1.25 μm per minute), respectively. Table 1 below lists the relevant data for all three samples.

[0104]

[0105]

[0106] As described above, etching of three samples of substrate 14a according to method 44 demonstrated the correlation between the temperature of etchant 18 and the etching rate. Figure 8 As shown, an Arrhenius plot is generated using three data points of the etch rate as a function of the temperature of the etchant 18. For this purpose, the natural logarithm of the Arrhenius equation can be described as In this equation, V is the etch rate (μm / hour); A is a constant; C is the concentration factor; E a is the activation energy (KJ / mol); R is the universal gas constant; and T is the temperature (in K). These three data points allow the generation of a linear trend line, which yields the equation ( Figure 8 The equation allows the calculation of the average etch rate as a function of temperature. Based on the slope of the trend line, E a Here the calculation is 107.3KJ / mol, and A×C is 1.27*10 13 μm / h.

[0107] according to Figure 8 The average etch rates obtained at various input temperatures were calculated using the equations given below. These are listed in Table 2 and are given in Fig. 9 As described above, as the temperature of the etchant 18 begins to exceed 250°C toward 275°C, the average etch rate becomes too fast to provide the thickness 12b in the third position 32 within a repeatable tolerance. Table 2 below lists the double-sided etch rates for various given temperatures of the etchant 18. The change in etch rate with temperature illustrates that, in embodiments, it is beneficial to keep the temperature constant while the etchant 18 contacts the substrate 14a.

[0108]

[0109] Prior to being subjected to method 44 (i.e., at first location 28), the glass-ceramic substrate of Sample 3 of this Example was tested to determine the normalized relative abundance of silicon in lithium, phosphorus, and aluminum in the composition of substrate 14a as a function of depth from first surface 36a to 500 nm (0.5 μm) in thickness 12a. The results are shown in Fig.10 After reducing the thickness 12 of the sample 3 while contacting the etchant 18 at the second location 30 and placing it at the third location 32 according to step 46 of method 44, the sample 3 is tested again to determine the silicon-normalized relative abundance of lithium, phosphorus, and aluminum in the substrate 14a as a function of depth from the first surface 36a to 500 nm (0.5 μm) in the thickness 12b. The results are shown in Fig.11 curve. Fig.10 and Fig.11 A comparison of the results reveals that the abundance of lithium in the composition of the substrate 14a before method 44 (at the first location 28) and after method 44 (at the third location 32) is substantially the same from the first surface 36a to a depth of 500 nm, particularly after normalization of the composition of the substrate 14a after entering the first 30-40 nm of the thickness 12 of the substrate 14a. Secondary ion mass spectrometry (SIMS) is a technique used to determine the silicon-normalized relative abundance of lithium, phosphorus, and aluminum in the composition of the substrate 14a as a function of depth, such as Fig.10 and 11 The curve shown.

[0110] Comparative Example 1: In Comparative Example 1, samples 4-8 of the same glass ceramic substrate as samples 1-3 used in the above examples were prepared. Instead of subjecting samples 4-8 to steps 46 and 48 of method 44, samples 4-8 were contacted with an aqueous NaOH solution etchant. Each of samples 4-8 was subjected to an aqueous NaOH solution of varying concentrations. The temperature of each aqueous NaOH solution varied as the concentration of NaOH in the aqueous solution varied. The higher the concentration of NaOH in the aqueous solution, the higher the temperature. For each of samples 4-8, a double-sided etch rate was determined. The results are listed in Table 3 below.

[0111]

[0112]

[0113] As disclosed in Table 3 above, the highest NaOH concentration (Sample 8) in the aqueous solution tested provided the fastest etching rate of 5.51 μm per hour. This fastest etching rate is much lower than the manageable etching rates of 174.5 μm per hour and 75.0 μm per hour for Samples 2 and 3 of the above-described embodiment that performs Method 44 and utilizes a molten mixture consisting of NaOH and KOH as the etchant 18. Even the slowest Sample 2's double-sided etching rate of 75.0 μm per hour is more than 13 times faster than the double-sided etching rate (5.51 μm per hour) of the fastest Sample 8 of Comparative Example 1. The fastest etching rate of 5.51 μm per hour (0.09 μm per minute) is much lower than the minimum of 1 μm per minute for double-sided etching according to Method 44.

[0114] The temperature of the aqueous solution used as an etchant is limited by the boiling point of the aqueous solution. In addition, the concentration of NaOH that can be dissolved in the aqueous solution is upper bounded at about 50 wt % to 60 wt %. Therefore, the highest possible temperature of the NaOH aqueous solution cannot exceed 132.5° C. by much. Samples 1-3 of the embodiment utilizing molten alkali metal salts allow significantly higher temperatures in the range of 225° C. to 300° C. The higher temperatures used in the present embodiment, compared to the comparative example, help explain the difference in etching rates achievable with molten alkali metal salts as etchant 18 and alkaline aqueous solutions as etchant 18.

[0115] Example 2: In Example 2, 50 mm×50 mm samples 9-19 of the same glass ceramic substrate as samples 1-8 used in the above examples were prepared. A molten mixture of 43 wt % NaOH and 57 wt % KOH was prepared as an etchant 18. The molten mixture was eutectic. The etchant 18 was placed in a container 16. The temperature of the etchant 18 was 222° C.

[0116] According to step 46 of method 44, sample 9 is moved from first position 28 to second position 30 in contact with etchant 18. Sample 9 is in contact with etchant 18 for a period of time until thickness 12 is reduced by about 53 μm. According to step 48 of method 44, sample 9 is then removed from contact with etchant 18. According to step 64 of method 44, etchant 18 remains disposed in container 16.

[0117] Steps 46, 48 are repeated sequentially for each remaining sample 10-19 according to step 64 of method 44. For each sample 9-19, the temperature of etchant 18 is maintained substantially constant within a range of 219.5° C. to 224° C. Each of samples 9-19 is contacted with etchant 18 for the same period of time.

[0118] Now refer to Fig.12 44, for each sample 9-19, the difference between the thickness 12a, 12b of the sample in the first position 28 before the step and the thickness 12a, 12b of the sample in the third position 32 after steps 46, 48 due to contacting the etchant 18 in the second position 30 remains relatively constant. The left axis ("removal") is the difference between the thickness 12a at the first position 28 and the thickness 12b at the third position 32 of each sample after contacting the etchant 18 at the second position 30. As described above, for sample 9, the thickness 12b at the third position 32 after method 44 is about 53 μm. For sample 19, the thickness 12b at the third position 32 is also about 53 μm, the same as sample 9. In other words, the etchant 18 is able to etch at about the same etching rate for all samples 9-19, and there is no observable drop in the etching rate from sample 9 to sample 19, even though samples 10-18 are etched between samples 9 and sample 19. The clarity of the etchant 18 remained the same after etching samples 9-19. The color of the etchant 18 gradually changed from colorless before etching sample 9 to bluish green after etching sample 19. The change in color may be caused by the transfer of zinc from the substrate 14a of samples 9-19 to the etchant 18.

[0119] Example 3: In Example 3, samples 20-22 of the same glass ceramic substrate as samples 1-19 used in the above examples were prepared. According to step 50 of method 44, each sample 20-22 was textured by sandblasting. Sample 20 was not etched by step 50 or other means, or was not tempered by ion exchange in step 62. According to step 62 of method 44, sample 21 was etched for 35 minutes in a molten salt bath of 43wt% NaOH and 57wt% KOH at 225°C. According to step 46 of method 44, sample 23 was etched for 7.3 hours in a 50wt% NaOH aqueous solution at 130°C instead of in a molten salt bath. The final thickness 12b was measured here using a micrometer, specifically a 293-242 micrometer distributed by Mitutoyo Corporation of Kawasaki, Japan.

[0120]

[0121] Then measure the various properties of sample 20-22. Specifically, the surface roughness is measured in terms of the above-mentioned RMS roughness (Rq) and roughness average (Ra). RMS roughness (Rq) is the root mean square average of the profile height in the entire evaluation length. These roughness values ​​are measured using an atomic force microscope, specifically an atomic force microscope controlled by a NanoNavi control station distributed by Seiko Instruments Inc. (Seiko Electronics Corporation in Chiba City, Japan). Transmission haze ("T-Haze") refers to the percentage of transmitted light scattered outside the angle cone of ± 4.0 ° according to the American Society for Testing and Materials (ASTM) D1003. Haze values ​​are measured using Haze-Guard haze test equipment (Elektron Technologies, PLC). For optically smooth surfaces, the transmission haze is usually close to zero. Haze values ​​are usually reported as haze percentages. "Transmittance" refers to the percentage of incident optical power transmitted through a sample over the entire visible light wavelength range according to ASTM D1003. The transmittance values ​​herein are measured using the Haze-Guard test equipment of Elektron Technologies, PLC, mentioned above. Transmittance is reported as a percentage (%). "Gloss" refers to the measurement of specular reflectance calibrated relative to a standard (e.g., a certified black glass standard) according to ASTM procedure D523, the entire contents of which are incorporated herein by reference. The gloss herein is measured using a goniophotometer, such as that available from the above-mentioned Rhopoint Instruments. Common gloss measurements are typically made at incident light angles of 20°, 60°, and 85°, with the most commonly used gloss measurements being made at 60° ("gloss-60" refers to this incident light angle measurement).

[0122]

[0123] Sample 21 etched with a molten alkali metal salt according to step 46 of method 44 obtained haze, transmittance, and gloss values ​​similar to sample 22 etched without method 44 and using an aqueous alkali solution. However, it took 35 minutes to etch sample 21 via step 46 of method 44, while it took 7.3 hours to etch sample 22 using an aqueous alkali solution. In other words, sample 21 achieved similar haze, transmittance, and gloss values ​​as sample 22, but the etching time required was less than 10%. Both etching processes resulted in an increase in the measured surface roughness value of sample 20.

[0124] Example 4: In Example 4, samples 23-26 of the same glass ceramic substrate as samples 1-22 used in the above examples were prepared. In step 62 of method 44, all samples 23-26 were tempered by ion exchange. Sample 23 was not textured by sandblasting or etched by any process. Sample 24 was not textured by step 50, but was etched in a molten salt bath of 43wt% NaOH and 57wt% KOH at 225°C for 35 minutes according to steps 46, 48 of method 44. Sample 25 was both textured by step 50 and etched in a molten salt bath of 43wt% NaOH and 57wt% KOH at 225°C for 35 minutes according to steps 46, 48 of method 44. Sample 26 was textured by step 50, but then etched in an aqueous solution of 50wt% NaOH at 130°C for 7.3 hours. Samples 24-26 were all etched to remove 20μm on both major surfaces.

[0125]

[0126] Reference now Fig.13 , and then each of the samples 23-26 was subjected to a ring-on-ring load failure test according to ASTM C1499. The ring-on-ring load failure test is a method for determining the surface strength of the first surface 36a of the substrate 14a. The first surface 36a is placed downward on the ring. The test was performed using an Instron 5967 universal testing machine. Fig.13 is a Weibull probability plot showing the probability of fracture of substrate 14a as a function of the load on substrate 14a. Note that sample 25 etched according to method 44 is slightly stronger than sample 26 etched in an aqueous NaOH solution. In addition, sample 24 etched according to method 44 has a similar strength to sample 23 that has not been etched in any manner.

[0127] It will be apparent to those skilled in the art that various modifications and variations can be made without departing from the spirit or scope of the claims.

Claims

1. A method for etching a substrate, comprising: contacting a substrate having a thickness with an etchant placed in a container for a period of time until the thickness is reduced by at least 2 µm and at an average rate of 1 µm per minute to 6.7 µm per minute, the etchant having a temperature of 170°C to 250°C and comprising a molten mixture of two or more alkali metal hydroxides, wherein the molten mixture does not intentionally contain water; and Contacting the substrate with the etchant is discontinued.

2. The method according to claim 1, further comprising: Prior to contacting the substrate with the etchant, texturing the surface of the substrate is increased.

3. The method according to claim 1, further comprising: After ceasing contacting the substrate with the etchant, the substrate is tempered.

4. The method according to claim 2, wherein: Increasing the texture of the surface of the substrate includes grit blasting the surface.

5. The method according to claim 3, wherein: Tempering the substrate includes subjecting the substrate to an ion exchange process.

6. The method according to claim 1, wherein: The etchant further comprises one or more of an alkali metal nitrate and an alkali metal sulfate.

7. The method according to claim 6, wherein: The alkali metal nitrate is one or more of KNO3 and NaNO3.

8. The method according to claim 6, wherein: The alkali metal sulfate is one or more of K2SO4 and Na2SO4.

9. The method according to claim 6, wherein: One or more of the alkali metal nitrate and the alkali metal sulfate comprises greater than 0 wt % to 95 wt % of the etchant.

10. The method according to claim 1, wherein: The etchant includes a molten mixture of NaOH and KOH.

11. The method according to claim 1, wherein: The etchant includes a molten mixture of 24 wt % to 72 wt % NaOH and 76 wt % to 28 wt % KOH.

12. The method according to any one of claims 1 to 11, wherein: The substrate is an alkali aluminosilicate glass substrate or an alkali aluminosilicate glass ceramic substrate.

13. The method according to any one of claims 1 to 11, wherein: The time range is between 5 minutes and 2 hours.

14. The method according to any one of claims 1 to 11, wherein: The substrate has a composition; and This method allows Na in the composition to be reduced from the surface to a depth of 1 μm in thickness. + , K + , Li + The weight percentage change of any one or more of the above is less than 5%.

15. The method according to any one of claims 1 to 11, wherein: The substrate has a composition; and This method allows Na in the composition to be reduced from the surface to a depth of 1 μm in thickness. + , K + , Li + The weight percentage change of any one or more of the above is less than 1%.

16. The method according to any one of claims 1 to 11, wherein: The substrate has a composition; and This method allows the Ca in the composition to be reduced from the surface to a depth of 1 μm in thickness. ++ Mg ++ The weight percentage change of any one or more of the above is less than 5%.

17. The method according to any one of claims 1 to 11, wherein: The substrate has a composition; and This method allows the Ca in the composition to be reduced from the surface to a depth of 1 μm in thickness. ++ Mg ++ The weight percentage change of any one or more of the above is less than 1%.

18. The method according to claim 1, wherein: The substrate is one of a plurality of substrates, each substrate having a thickness, and the method further comprises: maintaining the etchant disposed in the container; and For each remaining substrate in the plurality of substrates, in sequence: (a) contacting the substrate with the etchant disposed in the container for a period of time until the thickness is reduced by at least 2 μm and at an average rate of 1 μm per minute to 6.7 μm per minute; and (b) ceasing contact between the substrate and the etchant.

19. The method according to claim 18, wherein: The number of the plurality of substrates is at least 10 substrates.

20. The method according to any one of claims 18-19, wherein: Each of the plurality of substrates is formed from the same batch composition.

21. The method according to any one of claims 18-19, further comprising: Prior to contacting each remaining substrate in the plurality of substrates, texturing a surface of each remaining substrate in the plurality of substrates is increased.

22. The method according to any one of claims 18-19, further comprising: Each remaining substrate in the plurality of substrates is tempered by an ion exchange process.

23. A system for reducing the thickness of a substrate, comprising: container; an etchant disposed in the container, the etchant contacting a surface of the container, the etchant comprising a molten mixture of two or more alkali metal hydroxides, and the etchant having a temperature of 170° C. to 250° C., wherein the molten mixture does not intentionally contain water; and A substrate having a first position, a second position and a third position, wherein the substrate is not in contact with the etchant, the substrate is in contact with the etchant, the substrate is again not in contact with the etchant, and the thickness of the substrate in the first position is at least 2 μm greater than the thickness in the third position, and decreases at a rate of 1 μm per minute to 6.7 μm per minute in the second position.

24. The system of claim 23, wherein: The surface of the container that contacts the etchant is polytetrafluoroethylene.

25. The system of claim 23, wherein: The surface of the container that contacts the etchant is nickel.

26. The system of claim 23, wherein: The etchant includes a molten mixture of NaOH and KOH.

27. The system of claim 23, wherein: The etchant includes a molten mixture of 24 wt % to 72 wt % NaOH and 76 wt % to 28 wt % KOH.

28. The system according to any one of claims 23 to 27, wherein: The substrate is an alkali aluminosilicate glass substrate or an alkali aluminosilicate glass ceramic substrate.

29. The system according to any one of claims 23-27, further comprising: A heating element is in communication with the etchant.

30. The system according to any one of claims 23-27, wherein: The substrate has a region under compressive stress.

31. The system according to any one of claims 23-27, wherein: The thickness of the substrate in the third position is at least 20 μm less than the thickness of the substrate in the first position.

32. The system according to any one of claims 23-27, wherein: The substrate is in the second position for a period of 10 minutes to 30 minutes.

33. The system according to any one of claims 23-27, wherein: The etchant further comprises one or more of an alkali metal nitrate and an alkali metal sulfate.

34. A system according to any one of claims 23-27, wherein: The substrate also includes a first surface that is formed and contacts the etchant at the second location of the substrate, and When the substrate is in the third position, Na in the substrate composition at a depth of 1 µm from the first surface to the thickness + , K + , Li + The weight percentage of any one or more of the above is the same as the weight percentage of Na in the composition of the substrate from the first surface to a depth of 1 μm in the thickness when the substrate is in the first position. + , K + , Li + The weight percentage of any one or more of the above mentioned components differs by ±5%.

35. The system of any one of claims 23-27, wherein: The substrate also includes a first surface configured and contacting an etchant at a second location on the substrate, and When the substrate is in the third position, Ca in the substrate composition at a depth of 1 μm from the first surface is ++ Mg ++ The weight percentage of any one or more of the above is the same as the weight percentage of Ca in the substrate composition at a depth of 1 μm from the first surface to the thickness when the substrate is in the first position. ++ Mg ++ The weight percentage of any one or more of the above mentioned components differs by ±5%.

36. The system of any one of claims 23-27, further comprising: A plurality of substrates including the substrate, each of the plurality of substrates having a first position, a second position, and a third position, wherein the substrate is not in contact with the etchant, the substrate is in contact with the etchant, the substrate is again not in contact with the etchant, the thickness at the first position is greater than the thickness at the third position, and the thickness at the second position decreases at a rate of 1 μm per minute to 6.7 μm per minute.

Citation Information

Patent Citations

  • High strength glass-ceramics having petalite and lithium silicate structures

    US10189741B2

  • High strength glass-ceramics having petalite and lithium silicate structures

    US20160102010A1

  • Systems and methods for measuring the stress profile of ion-exchanged glass

    US9140543B1

  • High strength glass-ceramics having petalite and lithium silicate structures

    US9809488B2

  • Process for forming textured glass component with high bending strength

    US20180086662A1